Omnibus Law in the Perspective of Constitutionality and Legal Politics - Abdul Hakim Siagian (Universitas Negeri Gorontalo, 2021)
Overlapping norms in regulations, for example in the Natural Resources sector in terms of ease of investment, which previously had been sufficiently well regulated in the Law, many of the rules were cut through the omnibus law draft. The issues to be discussed are the constitutionality of the omnibus law concept in achieving legal certainty and usefulness in Indonesia. The research method used is normative juridical legal research. The results show that the omnibus law will also not interfere with the hierarchy of statutory regulations because the omnibus law is actually applied the same as the usual statutory regulation formation system. Apart from that, the omnibus law will also provide significant legal objectives in the form of legal certainty and usefulness compared to the normal law revision method (one by one).